The Quality of Financial Statements Antecedents and Consequences Towards Financial Accountability - Karyatni, Ni Made Dwi; Handajani, Lilik (International Journal of Social Science and Business, 2020)
Based on this research, low quality of financial statement presentation, especially regional government level accounting entity. Presentation of the financial statements of the Regional Government Unit was not fully appropriate with the Governmental Accounting Standards and Accounting Policies so that affects the accuracy of the information presented in the financial statements. Inaccurate financial reports has a negative impact to users in policy decision. This study aimed to test empirically the factors that affect the quality of the financial statements and the problems were faced by regional government unit (SKPD) in preparing the financial statements and the implications for the financial accountability. The population in this research was 292 respondents. The sample was determined by purposive sampling technique amount 97 respondents including the Financial Administration Officer (PPK) SKPD, PPK staff at 44 SKPD staff and staff in accounting staff and reporting on SKPKD. Data analysis was used on Partial Least Square (PLS). The findings of this study indicate that the quality of SKPD financial statements was affected by the application of completion of audit findings, but this study is not affected by the reconciliation, competence of human resources and the leadership support. Other findings indicate that the financial statements SKPD have implications for financial accountability. The implications of this study can contribute some ideas for the Central Lombok regency government to increase financial assistance to personnel managers through education and training so that it can make good quality in the financial statements and practical contribution in formulating the direction and policies related to the accountability of local government financial reporting.